A novel method for encoding and decoding based on enhanced parity-check-concatenated polar codes - Yan WANG; Shunlan LIU; Zhenzhen XI; Jianrong BAO (Dianxin kexue)
Polar codes have perfect coding and decoding performance as a kind of error correction code, which have become a standard coding scheme for 5G short code control channel. While the length of polar codes is short, its performance is not good enough. A novel method for encoding and decoding based on enhanced parity-check-concatenated polar codes was proposed. The enhanced check bit was set up after the parity-check (PC) bit to check the information bits with low channel reliability again, which could help path metric value prune the decoding path and improve the reliability of decoding path selection. The simulations reveal that the proposed method has better performance than cyclic redundancy check (CRC) concatenated polar codes and PC concatenated polar codes under the same channel, code length and code rate conditions. In additive white Gaussian noise channel, when the code length is 128, the code rate is 1/2 and the bit error rate is 10-3, the proposed method achieves a gain of about 0.3 dB over the PC codes cascaded polar codes, about 0.4 dB over the CRC assisted polar codes.